LATENT PROFILES OF INTOLERANCE OF UNCERTAINTY AND ANXIETY SENSITIVITY AMONG CHINESE POSTGRADUATE STUDENTS IN MALAYSIA: LINKS TO PSYCHOSOCIAL WELL-BEING AND COUNSELLING-RELEVANT INSIGHTS - Wang, Yanhui; Yeo , Kee Jiar; Shih , Hui Lee (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Psychosocial well-being is an important educational and counselling outcome for international postgraduate students who often face sustained academic and acculturative uncertainty. Although intolerance of uncertainty (IU) and anxiety sensitivity (AS) have been widely studied as risk factors, less is known about how these risks cluster within individuals. Using a person-centred approach, this study examined latent profiles based on prospective IU (IU-PA), inhibitory IU (IU-IA), and anxiety sensitivity–cognitive concerns (AS-CC) in Chinese postgraduate students in Malaysia (N = 396; PhD n = 288; Master’s n = 108). Latent profile analysis supported a three-profile solution—Low-Risk (39.9%), Moderate-Risk (40.7%), and High-Risk (19.4%)—showing a clear gradient in overall risk severity. Psychosocial well-being differed across profiles, F (2, 393) = 9.91, p < .001, and post-hoc comparisons indicated that the High-Risk group reported lower well-being than both the Low-Risk (d = 0.56) and Moderate-Risk groups (d = 0.50). Degree level was not associated with profile membership, suggesting that these risk configurations cut across master’s and PhD programmes. The findings point to a practical implication for university counselling and student support: brief screening on IU-PA, IU-IA and AS-CC may help identify a subgroup with compounded cognitive risk, for whom uncertainty-management and culturally responsive support can be prioritised.